Performance evaluation of direction of arrival (DOA) for linear array antenna design using multiple signal classification (MUSIC) algorithm in variation of displacement vectors and noise / Norhayati Hamzah - Hamzah, Norhayati (2007)
Wireless communication has gone through an explosive growth over the past decade, improved methods for utilizing the multipath wireless channel must be developed as the network capacity has increased and quality are required. The use of adaptive antenna arrays is one area that gives promise for improving capacity of wireless communication systems and provides improved safety through location capabilities. In simple terms, these array antennas can reduce the co channel interference and effectively utilize the bandwidth by steering a high gain in the direction of interest and low gains in the undesired directions. In Smart Antenna system, the intelligence of the system depends on the information collected, processed and implemented through an algorithm i.e. Multiple Signal Classification (MUSIC). The algorithm have been implemented in MATLAB software and a program was developed to investigate the power spectrum of a fixed samples, 100 with the number of elements 15 with the existence of noise. The estimated Direction of Arrival (DOA) involves correlation analysis of the array signals, eigenanalysis and signal or noise subspace formation. The MUSIC power spectrum level for Direction of Arrival (DOA) is vital at various displacement vectors and noise as to design the optimum linear antenna array with the use of computer software, Computer Simulation Technologies (CST) Microwave Studio.